Pollen morphology of species of the family Asteraceae Martinov in the “cerros” of “Campanha” of Rio Grande do Sul, Brazil - Radaeski, Jefferson Nunes (2017)
In this study, the morphology of pollen grains of 15 species of Asteraceae collected in the “cerros” of the “Campanha” of Rio Grande do Sul are presented. The aim of this investigation was provided characteristics for the identifi cation of pollen grain of the taxa of this family. The pollen grains of species from three “cerros” of “Campanha” of the State were characterized, collected in the Alegrete city (“Cerro do Tigre”) and Quaraí city (“Cerro do Jarau” and “Cerro da Tapera”). Besides the pollen grain morphological description, the data are compared to information of the pollen production and statistical analysis of the compare among pollen attributes of the species. The pollen description combined with other approaches demonstrated to be resource suitable for use in the identifi cation of palynomorph in the “Campanha” of the State, since the grouping or separation of taxa according to their morphological diff erences provide information that contribute for better characterize Asteraceae pollen family in Rio Grande do Sul.